Autologous hematopoietic stem cell transplantation in combination with immunoablative protocol in secondary progressive multiple sclerosis: A 10-year follow-up of the first transplanted patient - Obradović Dragana; Tukić Ljiljana; Radovinović-Tasić Sanja; Petrović Boris; Elez Marija; Ostojić Gordana; Balint Bela (Vojnosanitetski Pregled)
Introduction. Multiple sclerosis (MS) is an immunemediated disease of the central nervous system that affects young individuals and leads to severe disability. High dose immunoablation followed by autologous hemopoietic stem cell transplantation (AHSCT) has been considered in the last 15 years as potentialy effective therapeutic approach for agressive MS. The most recent long-time follow-up results suggest that AHSCT is not only effective for highly aggressive MS, but for relapsing-remitting MS as well, providing long-term remission, or maybe even cure. We presented a 10- year follow-up of the first MS patient being treated by immunoablation therapy and AHSCT. Case report. A 27-year-old male experienced the first symptoms - intermitent numbness and paresthesia of arms and legs of what was treated for two years by psychiatrist as anxiety disorder. After he developed severe paraparesis he was admitted to the Neurology Clinic and diagnosed with MS. Our patient developed aggressive MS with frequent relapses, rapid disability progression and transition to secondary progressive form 6 years after MS onset [the Expanded Disability Status Scale (EDSS) 7.0 Ambulation Index (AI) 7]. AHSCT was performed, cyclophosphamide was used for hemopoietic stem cell mobilization and the BEAM protocol was used as conditionig regimen. No major adverse events followed the AHSCT. Neurological impairment improved, EDSS 6.5, AI 6 and during a 10-year followup remained unchanged. Brain MRI follow-up showed the absence of gadolinium enhancing lesions and a mild progression of brain atrophy. Conclusion. The patient with rapidly evolving, aggressive, noninflammatory MS initialy improved and remained stable, without disability progression for 10 years, after AHSCT. This kind of treatment should be considered in aggressive MS, or in disease modifying treatment nonresponsive MS patients, since appropriately timed AHSCT treatment may not only prevent disability progression but reduce the achieved level of disability, as well.